Plowing at sea: Twenty years of diagnoses and attempts to reform and fight against corruption in the Peruvian justice system - Purizaga Vértiz, Luis Miguel (2021)
After the 1990s and with the return to democracy at the beginning of the new century, a series of attempts to reform the state were carried out in Peru. The justice system was no exception, since over the last twenty years diagnoses, reform proposals, and regulatory modifications were drawn up none of which unfortunately fulfilled the promise of transforming the system. At the gates of the Bicentennial and with a new reform project started in mid-2018, it is necessary to carry out a recount and balance of these twenty years of reform attempts, testing some of the possible reasons why these failed, were not implemented, or were sidelined in the public debate. In this article we prepare this account and balance, incorporating a conceptual framework necessary for thinking about corruption in our justice system.